Mapping land enclosures and vegetation cover changes in the surroundings of Kenya's Dadaab refugee camps with very high resolution satellite imagery. (25th November 2018) - Rossi, Massimiliano; Rembold, Felix; Bolognesi, Michele; Nori, Michele; Mureithi, Stephen; Nyberg, Gert
Abstract: The immediate surroundings of refugee camps in drylands are among the areas exposed to highest pressure on natural resources including vegetation and soil. Understanding the dynamics of land fencing in these areas is critical for sustainable camp management and can help to improve the knowledge about land management in drylands in general. Very high resolution satellite imagery provides a means to observe such areas over time and to document land cover and use changes. This study uses satellite images to map fenced areas, which can be divided into pastoral enclosures and the so called 'green belts' (areas fenced for afforestation) around the Hagadera Camp in Dadaab (Kenya). It then analyses change dynamics between 2006 and 2013, a period where the refugee camp has been subject to high oscillations in camp population, due to a combination of conflicts and droughts in Somalia. The applied methodology allows detailed fence mapping and shows a large increase in fenced area (56%) over the 7‐year period. Although new pastoral enclosures expanded into more densely vegetated surroundings, land cover density inside already fenced areas either decreased or remained stable. Green belt areas grew at a similar rate (58%) but did not show evidence of greening over time and their longer term success is strongly dependent on maintenance. The settlement area did also expand remarkably in the same time (65%), and human and animal movements in the surroundings intensified with a negative impact on vegetation density. The study could not fully investigate the socio‐economic drivers and impacts linked to the rapid increase of enclosures, which are inextricably linked to evolutions in local agro‐pastoral practices. However, by documenting spatial and temporal dynamics of fenced areas, it adds new evidence to their increasing relevance in rangeland management, and opens the way to a number of hypotheses, stimulating the debate about long‐term ecological and socio‐economic impact.